2015
DOI: 10.1002/we.1863
|View full text |Cite
|
Sign up to set email alerts
|

On the application of the Jensen wake model using a turbulence‐dependent wake decay coefficient: the Sexbierum case

Abstract: We present a methodology to process wind turbine wake simulations, which are closely related to the nature of wake observations and the processing of these to generate the so-called wake cases. The method involves averaging a large number of wake simulations over a range of wind directions and partly accounts for the uncertainty in the wind direction assuming that the same follows a Gaussian distribution. Simulations of the single and double wake measurements at the Sexbierum onshore wind farm are performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 20 publications
3
82
0
Order By: Relevance
“…where k w is the wake decay factor and the recommended values is k w = 0.4I a for the flat terrain under the neutral conditions [39]. As shown in Figure 12, the proposed model gives more accurate predictions for the mean velocity distributions under the different yawed conditions than those by the top-hat shape used in the Jimenez's model, which underestimates the velocity deficit in the center of the wake and overestimates them in the outside regions.…”
Section: Wake Model For Yawed Wind Turbinesmentioning
confidence: 91%
See 2 more Smart Citations
“…where k w is the wake decay factor and the recommended values is k w = 0.4I a for the flat terrain under the neutral conditions [39]. As shown in Figure 12, the proposed model gives more accurate predictions for the mean velocity distributions under the different yawed conditions than those by the top-hat shape used in the Jimenez's model, which underestimates the velocity deficit in the center of the wake and overestimates them in the outside regions.…”
Section: Wake Model For Yawed Wind Turbinesmentioning
confidence: 91%
“…where is the wake decay factor and the recommended values is = 0.4 for the flat terrain under the neutral conditions [39]. Figure 12 and a scale of turbulence intensity with the value of 0.3 in Figure 13, respectively.…”
Section: Wake Model For Yawed Wind Turbinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviour of T I with wind speed is mainly due to stability effects, which are more pronounced at the low wind-speed range. When selecting near-neutral conditions T I is nearly constant with wind speed for easterlies at Høvsøre (Peña et al 2015a). The figure also shows in the solid grey line an estimation of T I assuming σ U = 2.5u * , which, combined with Eq.…”
Section: Wind-turbine Sitingmentioning
confidence: 99%
“…On the basis of these findings the 'Høvsøre tall wind profile' cases were prepared and cover a range of stability, forcing and baroclinic conditions, which can be used to evaluate PBL models (Peña et al 2014a). Peña et al (2014b) used several of these cases to study the turning of the wind with height, and found that within the PBL and under barotropic conditions, the more stable the conditions the greater the wind at Høvsøre veered; under baroclinic conditions the wind could even turn anticlockwise.…”
Section: Boundary-layer Windsmentioning
confidence: 99%